Role of Preoperative Adrenergic Blockade with Doxazosin on Hemodynamic Control during the Surgical Treatment of Pheochromocytoma: A Retrospective Study of 48 Cases. Issue 11 (November 2013) - Conzo, Giovanni; Musella, Mario; Corcione, Francesco; Depalma, Maurizio; Stanzione, Francesco; Della-Pietra, Cristina; Palazzo, Antonietta; Napolitano, Salvatore; Pasquali, Daniela; Milone, Marco; Agostino-Sinisi, Antonio; Ferraro, Fausto; et al.
Authors evaluated the effects of selective adrenergic blockade by means of doxazosin on blood pressure in 48 patients operated on for pheochromocytoma by a multicenter retrospective study. Age, tumor size, surgical approach, and operative time were analyzed as predictive factors of intraoperative hypertensive crises. Forty-eight patients underwent adrenalectomy—four open surgery and 44 laparoscopic surgery—for pheochromocytoma of adrenal glands from 1998 to 2008 after preoperative administration of doxazosin. Perioperative cardiovascular status modifications and surgical medium- and long-term outcomes were analyzed. There was no mortality, conversion rate was 4.5 per cent, and morbidity rate was 8.3 per cent. Intraoperative hypertensive crises (180/ 90 mmHg or higher) were observed in 14.5 per cent (seven of 48) of patients and were treated pharmacologically with no aftermath. None of the examined variables influenced the occurrence of intraoperative hypertensive episodes. Postoperative hypotension (lower than 90/60 mmHg) was observed in four of 48 patients (8.3%) and was treated by crystalloids and hydrocortisone. In the surgical treatment of pheochromocytoma, the preoperative adrenergic blockade by doxazosin does not prevent intraoperative hypertensive crises. Nevertheless, in our series, they were of short duration and were not associated with major cardiovascular complications. Perioperative hemodynamic instability was managed bypreoperative pharmacological treatment, allowing low morbidity.